Analyzing the Application of the Privacy Design Model in WhatsApp - A Case Study - dos Santos, Mariana Aparecida; Prates, Raquel Oliveira; Villela, Maria Lúcia Bento (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The increasing number of online social networks (OSN) and information disclosure have increased privacy concerns. Thus, considering privacy in design time might be a good way to address these concerns. In this context, the Privacy Design Model (PDM) aims to support OSN designers to reflect about privacy de-sign aspects. In this study, PDM is applied to analyze the privacy in WhatsApp. Our results points to relevant aspects regarding privacy in instant messages OSNs, but wich are not (well) covered in PDM dimensions. Thus, we identified the need to a further investigation about PDM expressiveness and a possible model review.